Perivascular space and white matter hyperintensities in Alzheimer’s disease: associations with disease progression and cognitive function - Philine Marie Schirge; Robert Perneczky; Toshiaki Taoka; Adriana L. Ruiz-Rizzo; Ersin Ersoezlue; Robert Forbrig; Selim Guersel; Carolin Kurz; Matthias Brendel; Julian Hellmann-Regen; Josef Priller; Anja Schneider; et al. (Alzheimer’s Research & Therapy)
Abstract Background Alzheimer’s disease (AD) is the leading cause of dementia, characterized by the accumulation of amyloid-beta (Aβ) and neurofibrillary tangles. Recent studies emphasize the role of vascular factors, including the glymphatic system, in AD pathogenesis, particularly in Aβ clearance. The diffusion tensor image analysis along the perivascular space (DTI-ALPS; ALPS-Index) has emerged as a novel, non-invasive method to evaluate the glymphatic system in vivo, showing glymphatic insufficiency in AD. This study aimed to investigate alterations in the function of the glymphatic system in individuals with AD versus healthy controls (HC), and to explore its association with Aβ, cerebrovascular disease (CVD), white matter hyperintensities (WMH), and cognitive function. Methods DTI MRI data from three independent study cohorts (ActiGliA: AD n = 16, Controls n = 18; DELCODE: AD n = 54, Controls n = 67; ADNI: AD n = 43, Controls n = 49) were used to evaluate the perivascular space (PVS) integrity; a potential biomarker for glymphatic activity. The DTI-Along the Perivascular Space technique was used to measure water diffusion along PVS providing an index to assess the efficiency of the glymphatic system’s waste clearance function. WMH load was quantified in FLAIR MRI using the lesion segmentation tool. We quantified WMHs volume within our defined region of interest (ROI) and excluded participants with any WMHs to avoid confounding the ALPS-Index. Associations with cerebrospinal fluid (CSF) AD hallmark biomarkers, cognitive performance (MMSE) and clinical severity (CDR) were assessed. Results AD patients had a significantly lower ALPS-Index vs. healthy controls (ActiGliA: AD: mean = 1.22, SD = 0.12; Controls: mean = 1.36, SD = 0.14, p = 0.004; DELCODE: AD: mean = 1.26, SD = 0.18; Controls: mean = 1.34, SD = 0.2, p = 0.035; ADNI: AD: mean = 1.08, SD = 0.24; Controls: mean = 1.19, SD = 0.13, p = 0.008). The ALPS-Index was associated with CSF Aβ concentration, WMH number and MMSE and CDR. WMH, found in the ROIs correlated negatively with the ALPS-Index. Conclusions This study highlights the potential of the DTI-ALPS-Index as a biomarker for glymphatic dysfunction in AD. It underscores the importance of considering vascular factors and the glymphatic system in the pathogenesis and diagnosis of AD as WMHs in the ROI could cause disturbances and inaccurate indices.